THE EFFECTIVENESS OF EDUCATION AND TRAINING PROGRAMS FOR THE MTS’ ENGLISH TEACHERS - Hendri Hendri (Jurnal Dialog, 2018)
English Improving the quality of technical staffs of religious affairs or teachers has been an essential factor in the Human Resources development at the Ministry of Religious Affairs. An effective education and training programs can lead to the positive results that are concomitant with the intended goals. This study aimes to measure the effectiveness of education and training programs for English teachers at Religious Training Center Padang in 2017. It is based on descriptive quantitative method utilizing questionnaire and documentation techniques to collect the data. To analyze the effectiveness of education and training programs, Kirkpatrick’s theory is used to investigate responses, learning and behavior. This study found that the basic training for English Teachers which was by the Religious Training Center of Padang City from 14th up to 26th of September 2017 was conducted effectively at the success rate of 86,87%. Indonesia Peningkatan mutu tenaga teknis keagamaan atau tenaga pendidik menjadi poin penting dalam pengembangan kualitas Sumber Daya Manusia Kementerian Agama. Efektivitas dalam pendidikan dan pelatihan adalah suatu kegiatan yang dapat menghasilkan pengaruh yang tepat, akurat, dan sesuai dengan tujuan yang ingin dicapai. Penelitian ini bertujuan untuk mengetahui efektivitas pelaksanaan Pendidikan dan pelatihan Guru Mata Pelajaran Bahasa Inggris MTs Tingkat dasar Tahun 2017 di Balai Diklat Keagamaan Padang. Metode yang digunakan dalam penelitian ini adalah deskriptif kuantitatif dengan teknik pengumpulan data melalui Angket dan Studi Dokumentasi. Pengukuran efektivitas pendidikan dan pelatihan menggunakan metode/teori Kickpatrick yaitu reaksi (reaction) atau tanggapan, pembelajaran (learning) dan prilaku (behavior). Dapat disimpulkan bahwa Pendidikan dan Pelatihan Guru mata pelajaran bahasa Inggris MTs Tingkat Dasar Tahun 2017 yang dilaksanakan di kampus Balai Diklat Keagamaan Padang mulai tanggal 14 sampai dengan 26 September 2017 telah terlaksana dengan kategori efektif dengan persentase keberhasilan efektivitas 86,87%.